Perceptions of International Tourists on Internationalization of Hospital Services in Post-Pandemic Manado: A Hospital Service Marketing Approach - Lombogia, Christian Apolinaris; Umboh, Ivonne Angelic (Universitas Dian Nuswantoro Semarang, 2023)
This study aims to determine the impact of the internationalization of several types of A and B hospitals in Manado and its surroundings. The Ministry of Tourism declared Manado as one of the main destinations in Indonesia. How promote and bring in foreign tourists must be accompanied by security guarantees, the main ones being health insurance and access to international insurance when in tourist destinations. The research method was carried out by convenient purposive sampling at the inns and hotels of tourists. The results of the research stated that all foreign tourists have positive perceptions and beliefs about the existence and services of international hospitals in Manado; the thing that still makes them doubtful is the completeness of international standard hospital facilities. Still, these doubts can be overcome with reassurance with evidence.Keywords: Hospital Internationalization, Perception, Foreign tourist, hospital facilities